(untitled) (Fiep Bulletin - online, 2014)
The present work waives for the paradigm of the Education at the Distance to make possible the professional’s of the education autonomous formation, that identifies with the knowledge and he/she has commitment with the learning, to transcend the education universe where the unilateral systemization, mechanics, impels for a positioning static inflexible front to the new knowledge. Therefore we will look for to discuss starting from theoretical foundations, as he/she feels the learning process, formation, that originates a practice pedagogic static, that it despises the vision where each individual through the learning, is inserted in the world as active participant, when adapting of knowledge and techniques, that it makes possible to build him/her in his/her interior an universe of symbolic representations, indispensable to the critical positioning on the one that and as the school it reproduces knowledge, including the point of view of who teaches and of who learns. In way, that the teachers become, therefore, professionals of the education bearers of an information, knowledge collection that allow to focus them his/her ruled pedagogic practice in a hybrid system that make possible to make available the several technological resources to service of their students’ learning.